2005
DOI: 10.1017/s1074070800027152
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Horticultural Employees' Attitudes Toward Their Jobs: A Qualitative Analysis Based on Herzberg's Theory of Job Satisfaction

Abstract: Job satisfaction is likely the most studied work-related attitude and is assumed to influence a variety of behaviors. This study analyzes the job satisfaction of agricultural employees using Herzberg's theory, which is broadly employed in management. Fourteen horticultural businesses participated in case studies of labor-management practices. Fifteen nonsupervisory employee interviews were analyzed regarding job satisfaction. Components of job satisfaction relevant to horticultural employees were family-busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…The authors also identified characteristics not identified by Herzberg that affected motivation (Bitsch & Hogberg, 2005). Family values, and the belief that their employer is looking out for them and they have access to top management was found to increase motivation.…”
Section: Theoretical Frameworkmentioning
confidence: 90%
See 4 more Smart Citations
“…The authors also identified characteristics not identified by Herzberg that affected motivation (Bitsch & Hogberg, 2005). Family values, and the belief that their employer is looking out for them and they have access to top management was found to increase motivation.…”
Section: Theoretical Frameworkmentioning
confidence: 90%
“…Breslin, MacNab, Worthley, Kibigting, and Jukis (2005) found evidence of a possible motivational shift in Japan, with workers beginning to value lifetime employability over lifetime employment. Bitsch and Hogberg (2005) identified family-value style management as a motivator among horticulture workers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations